Application of nanosilica in reinforced concrete beams. Issue 5 (19th May 2022) - Mustafa, Tarek Sayed; El Hariri, Mohamed O.R.; Khalafalla, Mohamed S.; Said, Yasmin
Abstract : The partial replacement of cement with nanomaterials such as nanosilica (NS) particles in concrete improves its strength and other properties. In this study, the effect of NS as a partial replacement of cement for concrete mixes and concrete beams was examined. The studied response characteristics of reinforced concrete beams included the compressive strength, failure mechanisms, load-carrying capacity and load–deflection behaviour. The results showed that compressive strength increased with an increase in NS content up to 2.0% replacement of cement weight. The rate of increase in compressive strength was no longer significant beyond 2.0% replacement, indeed there was a slight decrease in compressive strength for NS content of 3.0%. The effect of increased NS content on the flexural behaviour of beams was also studied. Increased NS content led to increases in the first-cracking and ultimate loads and reductions in the deflection at cracking and ultimate load levels. No major differences in the structural response parameters were observed for test beams with zoning of NS in the bottom tension or top compression zones. An increase in NS content led to a slight increase in the ultimate strain associated with the ultimate load. Good agreement was found between experimental and theoretical ultimate moments.